Cognitive Load in Electromagnetic Navigational and Robotic Bronchoscopy for Pulmonary Nodules - Kapp, Christopher M. (ATS Sch, 2020)
Background: Electromagnetic navigational bronchoscopy (ENB) and robotic-assisted bronchoscopy (RB) require a high degree of decision-making and psychomotor skill. Cognitive load theory is the overall effort expended by individuals in response to a task and is closely related to the usability of devices for medical procedures. High cognitive workload leads to poor surgical outcomes and represents a bottleneck for learning that affects performance. Objective: To analyze the cognitive load associated with ENB and RB in experienced ENB practitioners learning RB. Methods: Six experienced ENB bronchoscopists performed ENB and RB on a human cadaver model of peripheral pulmonary nodules. To assess cognitive load, we used the Surgery Task Load Index (SURG-TLX) and biometric changes. The SURG-TLX questionnaire was given to the provider after every peripheral pulmonary nodule biopsy with ENB and RB. Pupillary dilation and screen changes were continuously measured throughout the procedure for each biopsy attempt to collect biometric measures of cognitive load. Procedural time and biopsy outcome were also recorded. Results: Forty procedures (ENB and RB) were analyzed. Task complexity (23%) and mental demand (21.4%) were the highest contributors to cognitive load in ENB and RB. The cumulative SURG-TLX was significantly lower for the RB (69.25 vs. 101.25; P < 0.01). Total procedure time was greater for ENB (6.7 min; SD 1.5) compared with RB (4.4 min; SD 1.5; P = 0.01). Pupillary diameter was similar across the modalities (RB vs. ENB), but the diameter was higher during the biopsy portion (4.25 mm) than the navigation portion (4.01 mm). Conclusion: The intrinsic cognitive load of RB was highly manageable by existing ENB practitioners, and in this study, RB appeared to be less mentally demanding. Future development and training should focus on task complexity and mental demand for RB. The biopsy portion, regardless of bronchoscopic modality, should be a focus for education and training.